Multilevel Network Analysis for the Social Sciences Theory, Methods and Applications - Lazega, Emmanuel; Snijders, Tom A.B (Methodos Series, Methodological Prospects in the Social Sciences, 2016)
VIII, 375 p. 65 illus., 41 illus. in color.